Summary of the Clinical Practice Guidelines for Penile Cancer 2021 by the Japanese Urological Association. (28th May 2022) - Yamaguchi, Takahiro; Sugiyama, Yutaka; Tanaka, Toshiaki; Kimura, Tomokazu; Yumura, Yasushi; Nakano, Masahiro; Sugiyama, Takayuki; Miura, Noriyoshi; Goya, Masato; Yamamoto, Akira; Takahashi, Satoru; Miura, Yuji; et al.
Abstract: Penile cancer is a rare cancer for which no medical guidelines have been established before in Japan. These guidelines aim to standardize, as much as possible, the therapeutic modality for penile cancer, for which empirical evidence is limited on a global scale, thereby bolstering therapeutic outcomes for patients with penile cancer. The new guidelines conform to the Minds Guide for Developing Clinical Practice Guidelines (2017) as much as possible. However, virtually no randomized comparative studies and meta‐analyses based on such randomized studies have been conducted. Therefore, only the findings available at present were listed after conducting an exhaustive literature review of items with extremely low evidence levels and for which bodies of evidence and grades of recommendation were not evaluated. Clinical questions were set for items with a relatively large number of studies, including retrospective studies. However, since it is virtually impracticable to summarize bodies of evidence by systematic reviews, recommendation grades and evidence levels were discussed and determined by the consensus panel of the Preparatory Committee. The following were outlined: epidemiological, pathological, diagnostic, therapeutic, follow‐up, and quality of life‐related findings. Additionally, seven clinical questions were established to determine recommendation grades and evidence levels. We hope that these guidelines will prove to be useful to medical professionals engaged in clinical practice related to penile cancer in Japan and anticipate that critical reviews of the guidelines will lead to further refinement of the next edition.